Extremes in a changing climate : detection, analysis and uncertainty - AghaKouchak, Amir. (Dordrecht : Springer, 2013)
'Extremes in a Changing Climate' presents both theoretical concepts and methodologies for detecting extremes, trend analysis, accounting for nonstationarities and uncertainties associated with extreme value analysis in a changing climate. The volume includes several climate case studies.
Includes bibliographical references and index.
Keywords: Climatic changes; Climatology